Accounting Indicators and their Impact on Market Prices of Shares of Commercial Banks Listed on the Amman Stock Exchange for the Period 2006-2017 - Almaaiteh, Wesam Abdulhamid; Alsaraireh, Ahmad Salim (International Review of Management and Marketing, 2019)
The study aimed at identifying the impact of some accounting indicators on the market price of share for the Jordanian commercial banks listed in Amman Stock Exchange (ASE)for the period 2006-2017. The study adopted STATA program in data processing and Random effect regression model was chosen to test the relationship between accounting indicators as independent variables include: return on equity (ROE), earnings per share (EPS), market price per share to book value per share (MPBV), dividend payout ratio (DPR), retained earnings per share (RPS), financial leverage (FL), current ratio (CR) and market price of share (MPS). The results show a positive and significant relationship between (ROE, EPS, MPBV, DPR) and MPS. Likewise, there is negative and significant relationship between retained earnings per share (RPS) and market price of share. On the other hand, the results show a negative and insignificant relationship between financial leverage(FL)and market price of share(MPS).The present study recommended that investors in Amman Stock Exchange (ASE) should be attention to the accounting indicators in general and (ROE, EPS, MPBV, DPR) in particular in order to build their investment decision. Keywords: Accounting indicators, Market price of share, Return on equity, Earning per share, Commercial Banks. JEL Classifications: G21, M41 DOI: https://doi.org/10.32479/irmm.8316